Determination of Trace Amounts of Nickel in Food and Environmental Water Samples by Flame Atomic Absorption Spectrometry after Dispersive Liquid-Liquid Microextraction - Mirabi, A.; Jamali, M.R.; Mehraeen, P.; Berijani, K. (Asian Journal of Chemistry, 2012)
The dispersive liquid-liquid microextraction was combined with the flame atomic absorption spectrometry for the determination of nickel in water samples. 4-Benzyl piperidine dithiocarbamate potassium salt (4-BPDC), chloroform and ethanol were used as chelating agent, extraction solvent and disperser solvent, respectively. In this extraction method, a mixture of 500 μL ethanol and 100 μL chloroform was rapidly injected by syringe into the water sample containing nickel ions and 4-BPDC. Thereby, a cloudy solution was formed. After centrifugation, these droplets were settled at the bottom of the conical test tube. The settled phase was separated using a micro-syringe and diluted to 100 μL with ethanol. A microsample introduction system was employed for the nebulization micro-volume of diluted solution into flame atomic absorption spectrometry. Some effective parameters on extraction, such as extraction and disperser solvent type and their volume, salt effect and pH have been optimized. The calibration graph was linear in the rage of 8-200 μg L-1 with detection limit of 2.2 μg L-1. RSD for ten replicate measurements was 1.9 %. The proposed method has been applied to the determination of nickel ions in food and environmental water samples with satisfactory results.